The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1152/physiolgenomics.00077.2015
|View full text |Cite
|
Sign up to set email alerts
|

Rodent models for resolving extremes of exercise and health

Abstract: The extremes of exercise capacity and health are considered a complex interplay between genes and the environment. In general, the study of animal models has proven critical for deep mechanistic exploration that provides guidance for focused and hypothesis-driven discovery in humans. Hypotheses underlying molecular mechanisms of disease and gene/tissue function can be tested in rodents to generate sufficient evidence to resolve and progress our understanding of human biology. Here we provide examples of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 100 publications
0
20
0
Order By: Relevance
“…The lines, termed the Low Capacity Runners (LCR) and the High Capacity Runners (HCR), differed by approximately 7-fold in running capacity after 27 generations of selective breeding. The sedentary HCR rats have increased mitochondrial content and function, are protected from the metabolic syndrome, hypertension, type 2 diabetes and cancer and have longer lifespan compared to the sedentary LCR rats (Garton et al, 2016). Since the HCR rats have metabolic phenotypes that resemble CR and DNA-PK-deficiency, we hypothesized that breeding for the HCR rats may have led to the generation of rats with decreased DNA-PK activity.…”
Section: Resultsmentioning
confidence: 99%
“…The lines, termed the Low Capacity Runners (LCR) and the High Capacity Runners (HCR), differed by approximately 7-fold in running capacity after 27 generations of selective breeding. The sedentary HCR rats have increased mitochondrial content and function, are protected from the metabolic syndrome, hypertension, type 2 diabetes and cancer and have longer lifespan compared to the sedentary LCR rats (Garton et al, 2016). Since the HCR rats have metabolic phenotypes that resemble CR and DNA-PK-deficiency, we hypothesized that breeding for the HCR rats may have led to the generation of rats with decreased DNA-PK activity.…”
Section: Resultsmentioning
confidence: 99%
“…Using an animal model of high‐ and low‐capacity running, or equivalently, high‐ and low‐aerobic capacity (Garton et al. ; Thyfault and Wright ), previous studies demonstrated that both maintaining high oxidative capacity and improving oxidative capacity via exercise protects against structural and functional consequences due to high‐fat diet induced metabolic challenge. Mice that are selectively bred for high aerobic capacity demonstrate less intramuscular lipid in the medial gastrocnemius when given a high‐fat diet compared to low‐aerobic capacity animals (Noland et al.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recovery time from exhaustive exercise is faster for individual fish with larger scope (Marras et al 2009). Similarly, selectively bred lines of rats with greater aerobic scope respond more to exercise training than do unselected lines, suggesting that greater aerobic scope may provide a reserve capacity that can be exploited when elevated activity is needed (Novak et al 2009;Garton et al 2016). Further, a fast-growing chicken strain possessed greater aerobic scope than a slow-growing strain (Konarzewski et al .…”
Section: Higher Aerobic Scope Can Provide Spare Capacitymentioning
confidence: 99%